KAUSALITAS PENERIMAAN, PENGELUARAN DAN PDRB PROVINSI DI INDONESIA 2010 – 2019 - Putra, Alno Sardi; Anis, Ali (Jurnal Kajian Ekonomi dan Pembangunan, 2021)
This study has three main objectives, namely, first to find out how the causal relationship between local government revenue and local government expenditure in provinces in Indonesia, the second objective is to find out how the causal relationship between local government expenditure and GRDP in provinces in Indonesia. Meanwhile, the third objective is to determine the causal relationship between local government revenue and GRDP in provinces in Indonesia. In this study, the objects in this study are 33 provinces throughout Indonesia. The data used are from 2010 to 2019. The data used are secondary data obtained from the Central Statistics Agency (BPS). The analytical method used is the VAR (Vector Auto Regression) time series analysis and the cluasaility granger test. which is processed using the help of Eviews. Based on the results of hypothesis testing, it shows that: (1) There is no causal relationship between local government revenue and local government expenditure in 33 provinces in Indonesia, but what is formed is a one-way relationship between government revenue and local government expenditure in 33 Indonesian provinces. In the hypothesis testing stage (2) there is no causal relationship between local government spending and GRDP in 33 provinces in Indonesia, in the analysis stage there is no one-way or two-way relationship between government spending and GRDP. Thus the hypothesis is rejected, while the results of hypothesis testing (3) There is no causal relationship between local government revenue and GRDP in 33 provinces in Indonesia. In the analysis stage, there is no one-way or two-way relationship between each variable. Thus the third hypothesis is rejected.